The lateral shift effect of gamma index evaluation on tomotherapy - Yosi Sudarsi Asril; Nuruddin Nasution; Wahyu Edy Wibowo; Supriyanto Ardjo Pawiro (Journal of Medical Physics and Biophysics, 2018)
Fourteen patients with different cases have been planned and treated using helical Tomotherapy HI-ART system. To investigate the lateral shift effect on gamma index, the planning verification was evaluated for a point dose and a fluence dose measurement using ion chamber and Gafchromic EBT3 film, respectively. As a result, the difference between a measured and calculated point dose was under 3% for all interest organs, which account for 1.46±0.71% (parotid), 1.97±0.56% (pelvis and abdomen), 2.27±0.24% (brain), 1.56±0.51% (nasopharynx), and 1.43±1.3% (breast). In addition, Gamma index criteria used to evaluate fluence dose was 3mm (distance-to-agreement) and 3% (dose-difference) with 90% passed rate. Overall, the results, found in this study, shows that a lateral shift of the patient table resulted in an error beyond an acceptable tolerance if the table was shifted at more than 3mm. Gamma index criteria, then, is met if the lateral shift was within 3mm.